Intellectual need for mathematical knowledge - Miežys, Vytautas (Lietuvos matematikos rinkinys, 2019)
Harel’s [2] notion of intel lectual need is refined by employing Davis’ [1] findings about interesting propositions in social sciences. A few hypothetical examples of how this revised definition might aid in planning mathematics lessons which provide meaningfulness for the students are presented.